Aspergillus Fumigatus ZnfA, a Novel Zinc Finger Transcription Factor Involved in Calcium Metabolism and Caspofungin Tolerance - Valero, Clara; Colabardini, Ana Cristina; de Castro, Patrícia Alves; Silva, Lilian Pereira; Ries, Laure Nicolas Annick; Pardeshi, Lakhansing; Wang, Fang; Rocha, Marina Campos; Malavazi, Iran; Silva, Roberto Nascimento; Martins, Celso; Domingos, Patrícia; et al. (Frontiers in Fungal Biology, 2021)
Invasive pulmonary aspergillosis is a life-threatening fungal infection especially in the immunocompromised patients. The low diversity of available antifungal drugs coupled to the emergence of antifungal resistance has become a worldwide clinical concern. The echinocandin Caspofungin (CSP) is recommended as a second-line therapy but resistance and tolerance mechanisms have been reported. However, how the fungal cell articulates the response to CSP is not completely understood. This work provides a detailed characterization of ZnfA, a transcription factor (TF) identified in previous screening studies that is involved in the A. fumigatus responses to calcium and CSP. This TF plays an important role in the regulation of iron homeostasis and cell wall organization in response to high CSP concentrations as revealed by Chromatin Immunoprecipitation coupled to DNA sequencing (ChIP-seq) analysis. Furthermore, ZnfA acts collaboratively with the key TF CrzA in modulating the response to calcium as well as cell wall and osmotic stresses. This study therefore describes the existence of an additional, previously unknown TF that bridges calcium signaling and the CSP cellular response and further exposes the complex connections that exist among different pathways which govern stress sensing and signalling in A. fumigatus.